2008
DOI: 10.1007/s11906-008-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Using health information technology to improve hypertension management

Abstract: High-quality medical care requires implementing evidence-based best practices, with continued monitoring to improve performance. Implementation science is beginning to identify approaches to developing, implementing, and evaluating quality improvement strategies across health care systems that lead to good outcomes for patients. Health information technology has much to contribute to quality improvement for hypertension, particularly as part of multidimensional strategies for improved care. Clinical reminders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This increased attention to the quality of BP care resulted in increased facility-level focus on BP control rates (and rewards for better rates). Some facilities have implemented the hypertension reminder described here, along with a decision support system for hypertension care, 38 or the provision of nurse-or pharmacist-administered behavioral interventions, 39,40 evidencing the VA's commitment to improving BP outcomes. However, the approach used here, whereby clinicians' counseling skills are enhanced through training, has rarely been used to improve BP care in VA. Our results suggest that such an approach, combined with the EMR reminder, could lead to small clinical gains at a relatively small cost for the clinician time required for such training.…”
Section: Resultsmentioning
confidence: 99%
“…This increased attention to the quality of BP care resulted in increased facility-level focus on BP control rates (and rewards for better rates). Some facilities have implemented the hypertension reminder described here, along with a decision support system for hypertension care, 38 or the provision of nurse-or pharmacist-administered behavioral interventions, 39,40 evidencing the VA's commitment to improving BP outcomes. However, the approach used here, whereby clinicians' counseling skills are enhanced through training, has rarely been used to improve BP care in VA. Our results suggest that such an approach, combined with the EMR reminder, could lead to small clinical gains at a relatively small cost for the clinician time required for such training.…”
Section: Resultsmentioning
confidence: 99%
“…While ambitious, similar changes are already occurring in treatment of hypercholesterolemia, where the ACC-AHA guidelines for treatment of patients with stable ischemic heart disease has recently removed its TTT component, 41 the VA system has changed its quality measures to be consistent with BTT, 42 and treatment decision support systems (though not BTT-based) already exist. 43 Before creating a public access decision tool for BTT, we feel it appropriate to await public vetting of our findings and perhaps await changes in formal guidelines and quality measures. Implementation of this work would be a major challenge, but given the importance of blood pressure treatment we feel that such discussions should be made a priority.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first specific DSS built for managing hypertension, the ATHENA-Hypertension (Assessment and Treatment of Hypertension: Evidence-based Automation built by Stanford Medical Informatics) system [13], a similar knowledge-based DSS like our built DSS, showed that implementation and deployment of clinical decision support was feasible in large clinical settings [14]. Differences in ATHENA system and DSS in drug management, prescription of antihypertensives, availability of physiological testing and risk classification are explained in detail in the File S1.…”
Section: Discussionmentioning
confidence: 99%